2000
DOI: 10.1002/(sici)1520-6327(200002)43:2<78::aid-arch4>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Allatotropic activity in the suboesophageal ganglia and corpora cardiaca of the adult male loreyi leafworm, Mythimna loreyi

Abstract: Allatotropic activity was found in the methanolic extract of the suboesophageal ganglia (SOG) and the corpora cardiaca (CC) of the Mythimna loreyi virgin males. No allatotropic activity was observed in the extract of brain or corpora allata (CA). Although CA can be activated by the SOG and CC extract, respectively, CC extract inhibited the response to the SOG extract. A significant in vitro allatotropic effect was exerted by the SOG and CC extract within 10 and 15 min, respectively, and this effect can be sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Mas‐AT stimulated JH synthesis in CA of M. sexta adults, and adults of the noctuid moths Heliothis virescens (Kataoka et al ., 1989), L. oleracea (Audsley et al ., 1999) and S. frugiperda (Oeh et al ., 2000), as well as L. oleracea larvae (Audsley et al ., 2000), but CA from the beetle Tenebrio molitor , the grasshopper Schistocerca gregaria , and the cockroach Periplaneta americana were not affected (Kataoka et al ., 1989). Mas‐AT increased JH synthesis in CA of adult male loreyi leafworm, Mythimna loreyi , but this effect was not significant (Kou & Chen, 2000). Therefore, it seems that CA‐activating effects by Mas‐AT are possibly limited to lepidopteran species (Hoffmann et al ., 1999; Oeh et al ., 2000).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mas‐AT stimulated JH synthesis in CA of M. sexta adults, and adults of the noctuid moths Heliothis virescens (Kataoka et al ., 1989), L. oleracea (Audsley et al ., 1999) and S. frugiperda (Oeh et al ., 2000), as well as L. oleracea larvae (Audsley et al ., 2000), but CA from the beetle Tenebrio molitor , the grasshopper Schistocerca gregaria , and the cockroach Periplaneta americana were not affected (Kataoka et al ., 1989). Mas‐AT increased JH synthesis in CA of adult male loreyi leafworm, Mythimna loreyi , but this effect was not significant (Kou & Chen, 2000). Therefore, it seems that CA‐activating effects by Mas‐AT are possibly limited to lepidopteran species (Hoffmann et al ., 1999; Oeh et al ., 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it seems that CA‐activating effects by Mas‐AT are possibly limited to lepidopteran species (Hoffmann et al ., 1999; Oeh et al ., 2000). Many other allatotropic factors have been found in several insect species, but none has yet been identified (Hoffmann et al ., 1999; Kou & Chen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of JH biosynthesis by the corpora allata of adult female Aedes aegypti in vitro: effect of farnesoic acid and Aedes allatotropin 1992), crickets Gryllus bimaculatus and Acheta domesticus (Lorenz and Hoffmann, 1995), true bug Pyrrhocoris apterus (Hodkova et al, 1996), Loreyi leafworm Mythimna loreyi (Kou and Chen, 2000) and the honey bee Apis mellifera (Gäde et al, 1997), so far only a single peptide has been chemically identified. This is the Manduca sexta allatotropin (Mas-AT) identified from heads of the pharate adult tobacco hornworm Manduca sexta (Kataoka et al, 1989), a 13-residue amidated peptide with the sequence GFKNVEMMTARGFamide that stimulates adult CA in vitro but does not affect the activity of larval or pupal CA (Kataoka et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…As in other lepidopteran moths, the brain and the SOG of the M. loreyi are fused to form a complex in the adult stage ( Copenhaver & Truman, 1986) . Although the allatotropic activity was found in methanolic extract of the SOG and CC ( Kou & Chen, 2000), the existence of peptidergic factor(s) in brain–SOG–CC extracts, which stimulate synthesis of JHA in vitro is reported in this study; and the effects of NCA I and NCA II on the allatotropic control of CA is also examined.…”
Section: Introductionmentioning
confidence: 80%
“…1989 ). In fact, further investigation showed that the source of the allatotropin might be the SOG or CC ( Kou & Chen, 2000). Further elucidation of the amino acid sequences of the allatotropins in this insect is now in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 99%